Self-Rehabilitation through Dance: An Ethnographic Study on Candy Girls Breast Cancer Survivor Group in Kuala Lumpur, Malaysia - Premalatha Thiagarajan; Mohammad Khairi Mokthar (Kajian Malaysia, 2022)
This study intends to examine a breast cancer survivor group called the Candy Girls. Candy Girls comprises 26 to 30 women (aged between 40 and 73 years), who are breast cancer survivors in the post-clinical phase. They all have successfully undergone various combinations of treatment such as lumpectomy, mastectomy, radiotherapy and chemotherapy for breast cancer and are on the path to recovery and post-recovery. In 2010, this group came together for a year-long research conducted by the Universiti Malaya’s Faculty of Medicine through the Department of Rehabilitation Medicine. Realising the benefits of exercise for the well-being of cancer survivors, Candy Girls decided to continue dancing on their own even after the completion of the research study. With the support of breast surgeons at the University of Malaya Medical Centre (UMMC), this group began a weekly three-hour self-administered exercise session, that is still, to this day, taking place every Saturday. Their activities focus primarily on dance. The group gradually expanded dance genres by incorporating line dance, Latin dances-based Zumba sessions, Malay folk dance forms such as joget and zapin, and Bollywood dance. While the multi-ethnic women are determined to stay healthy and happy through their weekly dance routines, they have made significant impact on women at large by performing dances at Breast Cancer Relays, Awareness Campaigns and Health Conferences. By engaging with this community of survivors, the researchers have not only been able to observe their activities but also to support them through additional yoga and dance trainings. The act of giving back to the community has further strengthened the researchers' relationship with the study subjects and has allowed deeper engagement with the community. This ethnographic research shows that dance as self-rehabilitation, not only enhances physical mobility and emotional well-being, but forges a strong group solidarity among the women as a much-needed support system for survivors.